NMR observation of HIV‐1 gp120 conformational flexibility resulting from V3 truncation. (3rd June 2014) - Moseri, Adi; Schnur, Einat; Noah, Eran; Zherdev, Yuri; Kessler, Naama; Singhal Sinha, Eshu; Abayev, Meital; Naider, Fred; Scherf, Tali; Anglister, Jacob
<x xml:space="preserve">Abstract</x> The envelope spike of HIV‐1, which consists of three external gp120 and three transmembrane gp41 glycoproteins, recognizes its target cells by successively binding to its primary CD4 receptor and a coreceptor molecule. Until recently, atomic‐resolution structures were available primarily for monomeric HIV‐1 gp120, in which the V1, V2 and V3 variable loops were omitted (gp120core), in complex with soluble CD4 (sCD4). Differences between the structure of HIV gp120core in complex with sCD4 and the structure of unliganded simian immunodeficiency virus gp120core led to the hypothesis that gp120 undergoes a major conformational change upon sCD4 binding. To investigate the conformational flexibility of gp120, we generated two forms of mutated gp120 amenable for NMR studies: one with V1, V2 and V3 omitted (mutgp120core) and the other containing the V3 region [mutgp120core(+V3)]. The TROSY‐1H‐15N‐HSQC spectra of [2H, 13C, 15N]Arg‐labeled and [2H, 13C, 15N]Ile‐labeled unliganded mutgp120core showed many fewer crosspeaks than the expected number, and also many fewer crosspeaks in comparison with the labeled mutgp120core bound to the CD4‐mimic peptide, CD4M33. This finding suggests that in the unliganded form, mutgp120core shows considerable flexibility and motions on the millisecond time scale. In contrast, most of the expected crosspeaks were observed for the unliganded mutgp120core(+V3), and only a few changes in chemical shift were observed upon CD4M33 binding. These results indicate that mutgp120core(+V3) does not show any significant conformational flexibility in its unliganded form and does not undergo any significant conformational change upon CD4M33 binding, underlining the importance of V3 in stabilizing the gp120core conformation.